Identifying agricultural expenditures within the public financial accounts and coding system in Ghana: Is the ten percent government agriculture expenditure overestimated? - Benin, Samuel (International Food Policy Research Institute, 2014)
This paper is part of four country case studies that take a detailed look at public expenditures in agriculture, and at how the data on expenditures are captured in government financial and budget accounts. The objective of these studies is to unpack the black box of public expenditure statistics reported in various cross-country datasets, and ultimately to enable the use of existing government accounts to identify levels and compositions of government agriculture expenditures, with better understanding of what these data are in fact accounting for.